BUSINESSES PRODUCING TERASI IN THE VILLAGE WEEK CHART ASAHAN TANJUNG BALAI KABUPATEN ASAHAN NORTH SUMATRA PROVINCE - Suci Adha Dalimunte; Muhammad Ramli; Hemdrik ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Research businesses producing terasi in the village week chart AsahanTanjung Balai Kabupaten Asahan North Sumatra Province , carried out in october2014 .The aim is to know the state of businesses producing terasi , large investmentand to know business profitability. Methods used which is a method with thedetermination of survey respondents were in census .Shrimp production terasi rebon produced by businessmen in a month on alarge scale reached 62920 kg and to a small scale reached 13000 kg with a totalinvestment on a large scale fund of Rp .1.743.600.000 - and to a small scale a totalinvestment amounting to Rp .460.800.000 . Based on business profitability obtainedvalue rcr a large scale namely 1.12 while a small scale that is 1,120 amp 960 rr alarge scale namely 0,114 while 0,414 a small scale amp 960 cr a large scale namely0,128 while 0,707 a small scale roi a large scale namely 2.05 and small slaka 584.Seen from the level of investment roi very low that is implanted moreover on alarge scale less efficient because of the large investment for operation arrest largerthan a small scale.Keywords : Terasi, Production, Businesses.